Structural criteria for identifying granitic cumulates - Vernon, R.; Collins, William (University of Chicago Press, 2011)
Cumulates are igneous rocks that reflect relative concentration of crystals and/or loss of melt and that therefore did not crystallize entirely from a magma of their current whole-rock composition. However, this definition does not help to identify cumulates, and so the problem is to determine whether the current whole-rock composition reflects cumulate processes, which is where structural criteria can be useful. Identification of cumulates in granitoids can be difficult, especially in the absence of major whole-rock compositional differences between cumulate and host. Structural and structural/mineralogical criteria diagnostic of, or at least consistent with, granitic cumulates include (1) locally high concentrations of particular minerals relative to concentrations in the bulk of the intrusion; (2) abundant euhedral crystals in contact, at least with regard to cores that touched before any overgrowths and consequent molding of minerals about each other occurred; (3) abundant antecrysts or mantled xenocrysts; (4) adjacent crystals of plagioclase with different zoning patterns; (5) crystal contact melting; (6) concentration of a wide variety of microgranitoid enclaves ("mafic inclusions") in a megacryst-rich granitoid; (7) interpenetration of microgranitoid enclaves between abundant feldspar crystals; (8) intricate penetration of fine-grained mafic aggregates between feldspar crystals; (9) granitoid devoid of or extremely poor in quartz, especially with a strong magmatic foliation, occurring beneath or between major enclaves; (10) mobilized crystal aggregates with interstitial liquid, forming local, intrapluton intrusions; (11) graded layering, channel fills, and cross-lamination involving concentrations (schlieren) of mafic minerals, in some instances with K-feldspar megacrysts and/or microgranitoid enclaves; (12) continuous and partly disintegrated sheets of more mafic magma in mafic and silicic layered intrusions (MASLI plutons); (13) layered, magmatically foliated pluton margins from which leucogranitic lenses have been squeezed, forming projections into the pluton; (14) marked, patchy, or streaky modal variation; (15) "glomeroporphyritic" aggregates, implying local concentration of crystals by either heterogeneous nucleation or synneusis; and (16) compositional similarity of minerals in the most and least mafic rocks of the pluton. The proportion of "interstitial" mineral conveys no information as to the amount of "trapped liquid" in "orthocumulates." Reliable application of these structural criteria requires ascertaining that magmatic structures have not been obliterated during slow cooling, as is often asserted. The common presence in granitoids of primary magmatic features indicates that magmatic structural evidence is not removed during cooling in the absence of external deformation or metamorphism and so that structural evidence is potentially useful for identifying granitic cumulates.